Numerical Solutions of Fractional Differential Equations - Avcı, İbrahim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Fractional analysis has almost the same history as classical calculus. Fractional analysis did not attract enough attention for a long time. However, in recent decades, fractional analysis and fractional differential equations become very popular because of its powerful applications. A large number of new differential models that involve fractional calculus are developed. For most fractional differential equations we can not provide methods to compute the exact solutions analytically. Therefore it is necessary to revert to numerical methods. The structure of this thesis is arranged in the following way. We begin by recalling some classical facts from calculus. Partically, we recall definition and some properties of gamma, beta and Mittag-Leffler function. Then, in Chapter 3, we introduce the fundamental concepts and definitions of fractional calculus. This includes, in particular, some basic results concerning Riemann–Liouville differentiation and integration, and basic properties of Caputo derivative. In Chapter 4 we discuss fractional variant of the classical second-order Adams–Bashforth–Moulton method. It has been introduced by K. Diethelm, A.D. Freed, and discussed in book by K. Diethelm. Keywords: R-L Fractional Derivative, Caputo Fractional Derivative, Adams-Bashforth- Moulton Method, Fractional Differential Equations

ÖZ : Kesirli analiz, klasik kalkülüs ile hemen hemen aynı tarihe sahiptir. Kesirli analiz uzun bir süre dikkat çekmemesine ra˘gmen son yıllarda güçlü uygulama alanları oldu˘gu ortaya çıktıktan sonra kesirli diferansiyel denklemler ile birlikte en popüler çalı¸sma alanları olmu¸stur. Bununla birlikte kesirli kalkülüsü de kapsayan çok sayıda diferansiyel model geli¸stirilmi¸stir. Birçok kesirli diferansiyel denklemlerin kesin çözümleri için analitik metodlar yetersiz kalmaktadır. Bu nedenle sayısal yöntemlere dönmek gerekmektedir. Bu tezin yapısı ¸su ¸sekilde düzenlenmi¸stir: Öncelikle klasik kalkülüsün bazı özellikleri hatırlatılacaktır. ˙Ikinci kısımda gamma, beta, mittag-leffler gibi bazı özel fonksiyonların tanım ve bazı özellikleri hatırlanacaktır. Daha sonra üçüncü bölümde kesirli analizin tanım ve temel kavramları tanıtılacaktır. Bu kısım Abel integral denkleminin çözüm ko¸sullarını, Riemann-Liouville kesirli integral ve türevinin temel sonuçlarını ve Caputo kesirli türevinin tanım ve bazı temel özelliklerini içermektedir. Dördüncü bölümde ise ikinci dereceden klasik Adams-Bashford-Moulton metodunun kesirli varyantını tartı¸sıp, hata analizini yapılacaktır. Bu method K. Diethelm ve A.D. Freed tarafından tanıtılmı¸s ve K. Diethelm tarafından yazılan kitapta bahsedilmi¸stir. Anahtar kelimeler: R-L Kesirli Turev, Caputo Kesirli Turev, Adams-Bashforth-Moulton Metodu, Kesirli Diferensiyel Denklemler.
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2014. Supervisor: Prof. Dr. Nazım Mahmudov.
Keywords: Mathematics; Fractional calculus - Differential equations; Differential equations - Numerical solutions; R-L Fractional Derivative; Caputo Fractional Derivative; Adams-Bashforth-Moulton Method; Fractional Differential Equations Moulton Method; Fractional Differential Equations